Content management on YouTube by Spanish think tanks - Gómez de Travesedo-Rojas, Ruth; Gil-Ramírez, Marta (Frontiers in Political Science, 2025)
The growing need for think tanks to effectively manage their communication in order to reach their stakeholders has forced them to implement communication strategies that go beyond offline media. The opportunities offered by social media are being exploited by these think tanks, which have found YouTube to be a suitable platform for sharing meaningful messages to their communities. This study uses quantitative and qualitative content analysis to examine how these think tanks manage this social network, with the aim of determining whether there are common patterns or whether each think tank has different strategies. To this end, a sample of 190 videos was analyzed, corresponding to the top 10 most viewed videos of 19 Spanish think tanks listed in the 2020 Global Go To Think Tank Index Report. The results show similarities in certain parameters, such as video length and language used, but significant differences in others, such as content themes and types. In conclusion, Spanish think tanks have considerable room for improvement in managing their content on YouTube, which could enable them to reach a larger audience. Increasing the level of interaction with users or adding subtitles in a language other than the one used would contribute positively to achieving this objective.